Taller and shorter - Watt, Fiona; Wells, Rachel; Figg, Non (London : Usborne Publishing Ltd, 2017)
Who is taller- Panda or Hippo? Is Meerkat shorter than Duck? And who is the tallest animal of all?
Keywords: Size perception -- Juvenile fiction -- Pictorial works; Size judgment -- Juvenile fiction